2017
DOI: 10.1016/j.sleep.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness and fatigue may indicate accelerated brain aging in cognitively normal late middle-aged and older adults

Abstract: Excessive daytime sleepiness (EDS) and fatigue increases with age. The aim of this study was to investigate the association between EDS and fatigue with cortical thickness and hippocampal volume in cognitively normal, late middle-aged and older adults. We performed a cross-sectional observational study of 1374 cognitively-normal subjects aged 50 years and older who had a structural MRI. Regional cortical thickness and hippocampal volume were measured. Multiple linear regression models were fit to explore assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 92 publications
6
78
2
1
Order By: Relevance
“…19,38,39 It is also possible sleepiness as measured by objective and subjective assessments and fatigue reflect different central nervous system processes with possibly different underlying neuroanatomic and neurophysiologic pathways. 40 For example, in late middleaged and older adults, subjective EDS is associated with reduction of global cortical thickness whereas fatigue is associated with reduction of frontal and temporal cortical thickness and hippocampal volume. 40 In this study, neither mBDI-II scores nor original scores of BDI-II were significantly associated with PVT performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,38,39 It is also possible sleepiness as measured by objective and subjective assessments and fatigue reflect different central nervous system processes with possibly different underlying neuroanatomic and neurophysiologic pathways. 40 For example, in late middleaged and older adults, subjective EDS is associated with reduction of global cortical thickness whereas fatigue is associated with reduction of frontal and temporal cortical thickness and hippocampal volume. 40 In this study, neither mBDI-II scores nor original scores of BDI-II were significantly associated with PVT performance.…”
Section: Discussionmentioning
confidence: 99%
“…40 For example, in late middleaged and older adults, subjective EDS is associated with reduction of global cortical thickness whereas fatigue is associated with reduction of frontal and temporal cortical thickness and hippocampal volume. 40 In this study, neither mBDI-II scores nor original scores of BDI-II were significantly associated with PVT performance. The lack of association between depression and PVT performance may be explained by the narrow range of depression scores in our samples.…”
Section: Discussionmentioning
confidence: 99%
“…Scores range from 0 to 24 (higher scores indicate more severe sleepiness) . In the current study, patient‐reported hypersomnia was established epidemiologically with a threshold of 10 or greater, previously validated in older populations and associated with adverse health outcomes . As a supplemental analysis, we also examined associations of patient characteristics with an ESS threshold of 11 or greater, which is more commonly used in younger age groups .…”
Section: Methodsmentioning
confidence: 99%
“…An early study that used the ESS in middle-aged adults found that greater sleepiness was associated with lower ventromedial prefrontal cortex volume [44], a region that is implicated in emotional regulation and decision making (see Figure 1)[45]. In a recent, large study of older adults (N=1,374), Carvalho et al [46] found that higher ESS scores not only related to lower cortical thickness in the frontal lobe, but also lower thickness in the parietal, temporal, and occipital lobes. An important question though is whether the daytime sleepiness (ESS) data reflected the presence of sleep apnea, general deficits in sleep quality, or the influence of non-sleep fatiguing factors.…”
Section: Structural Neuroimaging Studiesmentioning
confidence: 99%
“…Dusak et al [97] and Akhan et al [98] both observed that hippocampal volume was lower in sleep apnea participants than in healthy control participants. The hippocampal reductions related to a greater apnea-hypopnea index [98] and greater subjective sleepiness [46, 97, 99]. …”
Section: Neuroimaging Studies In Patients With Sleep Disordered Breatmentioning
confidence: 99%